APPLIED ASPECTS OF MODELING THE MULTI-CRITERIA CHOICE OF A UNIVERSITY - Anna Orlova (Вестник Северо-Кавказского федерального университета)
He article deals with the problems of modeling the choice of a higher educational institution by an entrant using the agent approach and system dynamics in the AnyLogic environment. The selection criteria that characterize the institution were identified. While modeling, the university was viewed as a system with a goal, as a vector of development. In the course of the work, factors that influenced the choice of university graduates with further modeling were revealed. The models are constructed in such a way that it is possible to see the graph of the dependence when the parameters change. The developed models allow you to see the choice from many preset parameters.